Failing Georgia—The Case Against the Ban on Social Promotion - Donald R. Livingston; Sharon M. Livingston (Arizona State University, 2002)
Our analysis begins with an examination of the state of Georgia's rationale for the decision regarding social promotion that was based on the perceived views that teachers have on the issue. Research suggests, however, that teachers hold contradictory opinions concerning the use of standardized tests for high stakes decisions, such as promotion, and are not aware of the consequences most children suffer when they fail a grade. Following a discussion that challenges the claims of success in Chicago, Baltimore, and Texas, we explore the viability of choosing litigation as a strategy to stop the use of high stakes tests given the adverse impact they have on protected minorities. From a study of the thirty-nine poorest counties in rural Georgia, the relationships between poverty, race and the Georgia Criterion Referenced Competency Test Results suggest that these tests do have an enormously disparate impact on impoverished African American children. Because chances for educational attainment will be severely limited by this test, most African American children will be discouraged from achieving a high school diploma. As a way to put a face on the data, a case study of a young girl who would probably fail her grade in school if the law was enforced is presented followed by recommendations that argue for changes in education policy and teaching. Rather than mandate a ban on social promotion, the state of Georgia should pursue improvement of socio-economic conditions, education policy and pedagogy.